2005
DOI: 10.1097/01.aog.0000150557.00298.47
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rapid Fetal Fibronectin in Predicting Preterm Delivery

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 10 publications
0
15
1
3
Order By: Relevance
“…Probabilistic sensitivity analysis gave an incremental cost (saving) of -£25.58 with a 2.5th and 97.5th percentile of -£304. 96 and £240.06, respectively, indicating substantial uncertainty. Sensitivity analyses showed that the admission rate had by far the largest impact on the final results.…”
Section: Methodsmentioning
confidence: 99%
“…Probabilistic sensitivity analysis gave an incremental cost (saving) of -£25.58 with a 2.5th and 97.5th percentile of -£304. 96 and £240.06, respectively, indicating substantial uncertainty. Sensitivity analyses showed that the admission rate had by far the largest impact on the final results.…”
Section: Methodsmentioning
confidence: 99%
“…85,[90][91][92][93] The methodological quality of the included primary studies is summarised in Figure 8 85 with a summary LR-of 0.50 (95% 0.43-0.59) (χ 2 heterogeneity test p = 0.00) ( Figure 13). A receiver operating characteristics (ROC) plot of sensitivity versus specificity for cervicovaginal fFN in symptomatic women is shown in Figure 14 and Figure 15.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Klinik pratikte en çok kullanılan biyokimyasal belirteç servikovaginal sıvıda fetal fibronektin ölçümüdür. Vaginal sıvıda fetal fibronektin mevcudiyeti doğumun başlayacağını göstermese de (PPD: %15-25); fibronektin saptanmaması 7 gün için-de doğumu NPD %99 üzerinde olacak şekilde dışlaya-bilmektedir [22]. Bu nedenle negatif sonuç doğum için düşük olasılık anlamına gelirken, pozitif sonuç hastanın doğum yapacağını göstermeyebilir.…”
Section: Discussionunclassified